Customized Orbit and Frontal Bone Implants - Wang, Weitao; Namin, Arya; Shokri, Tom; Ducic, Yadranko (Facial Plastic Surgery, 2020)
Orbitocranial reconstruction objectives include creation of a solid barrier between intracranial contents and the environment allowing restoration of physiologic homeostasis and restoration of aesthetic craniofacial contours. Historically, bone grafts have been used for reconstruction but were fraught with unpredictable resorption and imperfect contouring given the complex anatomy of the orbitofrontal bones. With advances in three-dimensional modeling technology, alloplastic custom implants in orbital and frontal bone reconstruction have allowed for rapid fixation reducing surgical times and improved cosmesis.
Keywords: cranioplasty; frontal; orbital; patient-specific implant